Peak nasal inspiratory flow: a comparative study in our day to day practice - Kumar, Vijay; ., Harshvradhan; Bhavana, Kranti; Bharti, Bhartendu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The peak nasal inspiratory flow is an objective measurement of nasal airway obstruction. It also helps in assessing response to treatment regardless of etiology. With this background this study was undertaken to establish diagnosis and monitoring treatment efficacy of PNIF in patients of allergic rhinitis and deviated nasal septum. Methods: This prospective observational study involved 150 subjects who were selected among the patients attending the outpatient department of ENT and Head-Neck surgery, All India Institute of Medical Sciences, Patna. Thorough history was taken of all patients followed by general systemic and ENT examination. Each subject was asked to complete a SNOT 20 questionnaire. SPSS software was used for data analysis. Results: Out of total 150 subjects, 50 had deviated nasal septum (DNS), 50 had allergic rhinitis and 50 were normal subjects. Normal subjects had mean PNIF value 80 liter per minute with a range of minimum to maximum; 60 L/min to 150 L/min. Patients with symptomatic deviated nasal septum (DNS) had mean PNIF value 50 L/min with a range 20–80 L/min. Patients with symptomatic allergic rhinitis had mean PNIF value 65 L/min with a range of minimum 40 L/min to maximum 90 L/min. Conclusions: On OPD basis, measurements of PNIF using Youlten peak flow meter can easily suggest anatomical & pathological variations in the nose and nasal cavity and can correlated well with patient’s symptoms and severity.